Improving Density and Efficiency of Infrared Projectors - Miguel Hernandez; Joshua Marks; Edwid Koerperick; Peyman Barakhshan; Garrett Ejzak; Kassem Nabha; John Prineas; Fouad Kiamilev (IEEE Photonics Journal, 2019)
Infrared scene projectors using LEDs instead of resistor arrays are a new technology that is gaining popularity within the infrared projection community. This paper describes two approaches to increase spatial resolution, pixel density, and efficiency of LED arrays using OnSemi .18 transistor technology.